THE ROLE OF CHARACTER COMPETENCY VALUE AND PERCEIVED USEFULNESS AS MEDIATORS OF VIRTUAL ITEM VALUE ON REPURCHASE INTENTION - Chandra, Rama; Syamsuar, Ginanjar; Megayani, Megayani; S, Dwi Windu; Mufid, Zhafran (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
This research aims to determine the role of character competency values and perceived usefulness as mediators of virtual item values on intention in repurchasing Mobile Legends skins. The population in this study were Mobile Legends Jabodetabek game players, with the sample criteria being Mobile Legends game players who had purchased skins in the last year. Data collection used a questionnaire distributed using Google Form via Whatsapp, and data analysis used SEM_PLS path analysis. The research results show that the value of virtual items has a positive effect on repurchase intention, character competency and perceived usefulness. The character competency value also has a positive effect on repurchase intention. However, character competency value does not mediate the effect of virtual item value on repurchase intention. Perceived usefulness has no effect on repurchase intentionand is also not a mediator of virtual item value on Mobile Legend players' intentionin repurchasing skins